Cattail wool fiber-based composite diaphragm as well as preparation method and application thereof

By using wool fibers and qualitative filter paper to prepare composite separators, the shortcomings of existing sodium ion battery separators in chemical stability, thermal stability and electrochemical performance are solved, and cost reduction and performance improvement are achieved. They are suitable for sodium ion batteries. Industrial application.

CN119481575APending Publication Date: 2025-02-18HEFEI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685644.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery separators have shortcomings in chemical stability, thermal stability, mechanical strength, electrolyte wetting and loading rate, and are relatively expensive, making it difficult to meet the needs of sodium ion batteries.

Method used

The composite separator is prepared by using wool fibers and qualitative filter paper. Through high-temperature soaking and filtration treatment, the dispersion and binding force of the wool fibers are improved to form a composite separator with good mechanical and electrochemical properties.

Benefits of technology

The comprehensive performance improvement of sodium ion battery separators in ionic conductivity, electrolyte loading rate, tensile strength, electrochemical stability and thermal stability is achieved, reducing production costs, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481575A_ABST
    Figure CN119481575A_ABST
Patent Text Reader

Abstract

The invention discloses a cattail wool fiber-based composite diaphragm and a preparation method and application thereof, and belongs to the technical field of battery materials, the preparation method of the cattail wool fiber-based composite diaphragm comprises the following steps: dispersing cattail wool in a sodium hydroxide solution, and performing high-temperature soaking to obtain a first dispersion liquid; filtering the first dispersion liquid, dispersing the filtered first dispersion liquid in a hydrogen peroxide solution, and performing high-temperature soaking to obtain a second dispersion liquid; filtering and drying the second dispersion liquid to obtain cattail fibers; taking cattail wool fibers and qualitative filter paper, and dispersing the cattail wool fibers and the qualitative filter paper into a solvent to obtain a composite suspension; and sieving and drying the composite suspension to obtain the cattail wool fiber-based composite diaphragm. The cattail wool fiber-based composite diaphragm prepared by the method has the comprehensive characteristics of simplicity and convenience in raw material acquisition, low cost, high electrolyte loading rate, high ionic conductivity, good mechanical property, high interface stability and the like, and has excellent cycling stability and high rate capability when being used for a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a cattail fiber-based composite diaphragm and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries, which are characterized by low cost and high safety, have become a new type of secondary battery after lithium-ion batteries and have attracted much attention in the energy storage market. Similar to the structure of lithium-ion batteries, sodium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes and diaphragms. Among them, the diaphragm plays the role of isolating the positive and negative electrodes, storing electrolytes and allowing sodium ions to shuttle, accounting for 10% to 20% of the total cost of the battery. The ideal diaphragm should have excellent chemical stability, thermal stability, mechanical strength, electrolyte wettability and loading rate, and have high porosity but small pore size, high ionic conductivity but small thickness, and low raw material cost.

[0003] At present, the commonly used sodium ion battery separators mainly include glass fiber separators, polyolefin separators and composite separators. Glass fiber separators have the advantages of good stability, high porosity and high ion conductivity, but their thickness, poor mechanical properties and high price make them only used in scientific research. Polyolefin separators have the characteristics of small thickness, low cost, excellent mechanical properties and good chemical stability, but they are insufficient in thermal stability, ionic conductivity and wettability to sodium ion battery electrolyte. The composite separator prepared by coating one or more layers of functional materials (such as oxide powder) with glass fiber separator or polyolefin separator as the base membrane can achieve a balance of mechanical properties, thermal stability and cost to a certain extent, but this may cause the base membrane surface to be dense, the thickness to increase and the internal resistance to increase, which will have a negative impact on the battery performance. In addition, some composite processes are relatively complex, which is not conducive to the large-scale application of composite separators.

[0004] As a biodegradable material with abundant resources in nature, cellulose has good chemical stability, mechanical properties and film-forming characteristics, and is low in cost, making it very suitable as a raw material or modified component for the preparation of diaphragms. At present, the main material of cellulose-based diaphragms is usually cellulose nanofibers. The strong interaction between the intermolecular hydrogen bonds makes the nanofibers tend to remain closely arranged during the film-forming process, resulting in the densification of the membrane structure. Densified membranes have problems such as low porosity, low electrolyte loading rate and poor ion conductivity, which will seriously affect the cycle stability and high-rate performance of the battery. Summary of the invention

[0005] The object of the present invention is to provide a cattail fiber-based composite diaphragm and a preparation method and application thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0007] A method for preparing a cattail fiber-based composite diaphragm comprises the following steps:

[0008] Dispersing cattail wool in a sodium hydroxide solution and soaking it at high temperature to obtain a first dispersion;

[0009] After filtering the first dispersion, the dispersion is dispersed in a hydrogen peroxide solution and immersed at high temperature to obtain a second dispersion;

[0010] The second dispersion is filtered and dried to obtain cattail fibers;

[0011] The cattail fibers and the qualitative filter paper are dispersed in a solvent to obtain a composite suspension;

[0012] The composite suspension is sieved and dried to obtain a cattail fiber-based composite diaphragm.

[0013] Preferably, the method for obtaining cattail wool comprises the following steps:

[0014] Scrape off the surface layer of the cattail sticks and remove the roots to get the cattail fluff.

[0015] Preferably, in the step of dispersing the cattail wool in a sodium hydroxide solution and subjecting the cattail wool to high temperature soaking, the temperature of the high temperature soaking is 90-100°C.

[0016] Preferably, the sodium hydroxide solution is an aqueous solution of sodium hydroxide, and its mass concentration is 1%-5%; the material-liquid ratio of cattail wool to the sodium hydroxide solution is 1-25 g / L.

[0017] Preferably, after filtering the first dispersion, it is dispersed in a hydrogen peroxide solution and then soaked at high temperature: the filtering method is to place the first dispersion in a sieve with a pore size of 200-400 mesh and rinse it with deionized water; the high temperature soaking temperature is 90-100°C.

[0018] Preferably, the hydrogen peroxide solution is an aqueous solution of hydrogen peroxide, and its mass concentration is 3%-5%; the material-liquid ratio of cattail wool to hydrogen peroxide solution is 1-50 g / L.

[0019] Preferably, the solvent is deionized water; the total concentration of cattail fiber and qualitative filter paper in the composite suspension is 1.5-15 g / L; the absolute dry weight ratio of cattail fiber and qualitative filter paper in the suspension is 1:9-7:3.

[0020] Preferably, in the steps of sieving and drying the composite suspension, the aperture of the sieve used for sieving is 200-400 mesh; the drying method is to dry at 25-50°C and then to dry in vacuum at 70-100°C.

[0021] Another object of an embodiment of the present invention is to provide a cattail fiber-based composite diaphragm prepared by the above-mentioned preparation method.

[0022] Another object of an embodiment of the present invention is to provide an application of the cattail fiber-based composite membrane in a sodium ion battery.

[0023] The present invention provides a method for preparing a cattail fiber-based composite membrane, in which micron cattail fibers with a large-area groove structure are extracted from cattail sticks. Compared with nanocellulose fibers that are easily arranged tightly and micron glass fibers with smooth surfaces, cattail fibers are more conducive to electrolyte absorption and storage. The cattail fiber-based composite membrane prepared using the cattail fiber and qualitative filter paper has good comprehensive performance in terms of ion conductivity, electrolyte loading rate, tensile strength, electrochemical stability, and thermal stability. The sodium ion battery assembled using the cattail fiber-based composite membrane prepared by the present invention exhibits excellent cycle stability and high rate performance.

[0024] Cattails are widely distributed in nature, and the qualitative filter paper with cellulose components used is also cheap and easy to obtain, so the cattail fiber-based composite diaphragm prepared by the present invention has a significant cost advantage.

[0025] In addition, the preparation method provided by the present invention has a simple process, high production efficiency, low equipment requirements, and is suitable for large-scale industrial production; by adjusting the composite ratio of cattail fiber and qualitative filter paper, the concentration of the suspension, etc., the thickness, porosity, micromorphology, etc. of the composite diaphragm can be optimized. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of extracting cattail fluff from cattail sticks in Example 1;

[0027] Figure 2 This is a component analysis diagram of the cattail-based cellulose composite diaphragm prepared in Example 1;

[0028] Figure 3 This is a surface morphology of the cattail fiber-based composite diaphragm prepared in Example 1;

[0029] Figure 4 is a cross-sectional view of the cattail fiber-based composite diaphragm prepared in Example 1;

[0030] Figure 5 is a cross-sectional view of the cattail fiber-based composite diaphragm prepared in Example 2;

[0031] Figure 6 is a cross-sectional view of the cattail fiber-based composite diaphragm prepared in Example 3;

[0032] Figure 7 This is a surface morphology of the glass fiber-based composite diaphragm prepared in Comparative Example 1;

[0033] Figure 8 This is a graph showing the electrolyte wettability test results of the cattail fiber-based composite diaphragm prepared in Example 1-3;

[0034] Fig. 9 The graph is a test result of the cycle performance of the cattail fiber-based composite membrane prepared in Examples 1-3 and the existing glass fiber membrane;

[0035] Fig.10 The figure is a graph showing the rate performance test results of the cattail fiber-based composite diaphragm prepared in Examples 1-3 and the existing glass fiber diaphragm. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] In one embodiment of the present invention, a method for preparing a cattail fiber-based composite membrane is provided, which comprises the following steps:

[0038] Dispersing cattail wool in a sodium hydroxide solution and soaking it at high temperature to obtain a first dispersion;

[0039] After filtering the first dispersion, the dispersion is dispersed in a hydrogen peroxide solution and immersed at high temperature to obtain a second dispersion;

[0040] The second dispersion is filtered and dried to obtain cattail fibers;

[0041] The cattail fibers and the qualitative filter paper are dispersed in a solvent to obtain a composite suspension;

[0042] The composite suspension is sieved and dried to obtain a cattail fiber-based composite diaphragm.

[0043] In practical applications, the cattail is the ear of Typha longibracteata of the Typhaceae family or various plants of the same genus; the cattail fluff is the part between the surface of the cattail and the root, and its length is within the range of 1 / 4-7 / 8 of the distance from the surface.

[0044] Specifically, the method for obtaining cattail fluff includes the following steps: scraping off the brown surface layer of the cattail stick, then removing the root, and scraping off the cattail fluff within the range of 1 / 4 to 7 / 8 of the length from the surface layer to the root.

[0045] In a preferred embodiment of the present invention, cattail wool is dispersed in a sodium hydroxide solution and subjected to a high-temperature soaking step: the high-temperature soaking temperature is 90-100° C. and the time is 1-6 hours.

[0046] In a preferred embodiment of the present invention, the sodium hydroxide solution is an aqueous solution of sodium hydroxide, which is used to remove hemicellulose, lignin and other components in cattail fluff, and its mass concentration is 1%-5%; the material-liquid ratio of cattail fluff to sodium hydroxide solution is 1-25g / L.

[0047] In a preferred embodiment of the present invention, the first dispersion is filtered and then dispersed in a hydrogen peroxide solution, and then immersed in a high temperature step: the filtering method is to place the first dispersion in a sieve with a pore size of 200-400 mesh and rinse with deionized water; the high temperature immersion temperature is 90-100° C. and the time is 1-6 hours.

[0048] In a preferred embodiment of the present invention, the hydrogen peroxide solution is an aqueous solution of hydrogen peroxide, which can bleach cellulose and has a mass concentration of 3%-5%; the material-liquid ratio of cattail wool to hydrogen peroxide solution is 1-50 g / L.

[0049] In a preferred embodiment of the present invention, in the step of filtering and drying the second dispersion: the filtering method is to place the second dispersion sample in a sieve with a pore size of 200-400 mesh and rinse it with deionized water; the drying method is to place it in a vacuum drying at a temperature of 60-80°C.

[0050] In a preferred embodiment of the present invention, the above-mentioned solvent can be deionized water, and of course other solvents that can evenly disperse the cattail fibers and the qualitative filter paper can also be used; the total concentration of the cattail fibers and the qualitative filter paper in the composite suspension is 1.5-15g / L; the absolute dry weight ratio of the cattail fibers and the qualitative filter paper in the suspension is 1:9-7:3, preferably 1:2-2:1.

[0051] In practical applications, the single preparation volume of the composite suspension is 500-1000 mL; the above-mentioned dispersion method is to stir at a speed of 10000-12000 rpm for 20-60 minutes.

[0052] In a preferred embodiment of the present invention, in the step of sieving and drying the composite suspension: the mesh used for sieving has an aperture of 200-400 mesh and a diameter of 20 cm; the drying method is to dry it at a temperature of 25-50° C. for 6-12 hours, and then to vacuum dry it at a temperature of 70-100° C. for 12-24 hours.

[0053] The thickness of the cattail fiber-based composite diaphragm prepared by the preparation method can be adjusted in the range of 30-180 microns.

[0054] In another embodiment of the present invention, there is also provided an application of the above-mentioned cattail fiber-based composite membrane in a sodium ion battery; specifically, a sodium ion battery, which at least includes a positive electrode, a negative electrode and an electrolyte, and also includes the above-mentioned cattail fiber-based composite membrane.

[0055] In the embodiment of the present invention, micron cattail fibers with large-area groove structures are extracted from cattails. Compared with the nanocellulose fibers that are easily arranged tightly and the micron glass fibers with smooth surfaces, cattail fibers are more conducive to electrolyte absorption and storage. In addition, compared with other plant fibers, the "groove" structure of cattail fibers is the most obvious, and the grooves are regular; while other plant fibers often have smooth surfaces, which are closer to glass fibers; therefore, cattail fibers are used in the embodiment of the present invention to prepare battery separators.

[0056] The following embodiments are some specific implementation cases of the present invention in practical applications, but are not limited thereto.

[0057] Embodiment 1: This embodiment provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0058] S1: Scrape off the brown surface of the cattail, then remove the root, and scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root (such as Figure 1 As shown), and use a balance to weigh the mass;

[0059] S2: Prepare equal volumes of 2.5% sodium hydroxide aqueous solution and 3% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to a solid-liquid ratio of 12.5 g / L to sodium hydroxide aqueous solution, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 70°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0060] S3: Weigh the cattail fiber and the ordinary qualitative filter paper in a ratio of 2:1 in absolute dry weight, add them into 500 mL of deionized water, and stir them for 30 minutes using a high-speed stirrer at 10,000 rpm to obtain a composite suspension with a concentration of 2 g / L;

[0061] S4: The composite suspension is poured onto a 350-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 40° C. for 8 hours, and then vacuum dried at 80° C. for 12 hours to obtain a cattail fiber-based composite diaphragm.

[0062] Example 2: This example provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0063] S1: Scrape off the brown surface of the cattail, then remove the root, and scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root (such as Figure 1 As shown), and use a balance to weigh the mass;

[0064] S2: Prepare equal volumes of 2.5% sodium hydroxide aqueous solution and 3% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to a solid-liquid ratio of 12.5 g / L to sodium hydroxide aqueous solution, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 70°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0065] S3: Weigh the cattail fiber and the ordinary qualitative filter paper in a ratio of 1:1 in absolute dry weight, add them into 500 mL of deionized water, and stir them for 30 minutes using a high-speed stirrer at 10,000 rpm to obtain a composite suspension with a concentration of 2 g / L;

[0066] S4: The composite suspension is poured onto a 350-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 40° C. for 8 hours, and then vacuum dried at 80° C. for 12 hours to obtain a cattail fiber-based composite diaphragm.

[0067] Embodiment 3: This embodiment provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0068] S1: Scrape off the brown surface of the cattail, then remove the root, and scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root (such as Figure 1 As shown), and use a balance to weigh the mass;

[0069] S2: Prepare equal volumes of 2.5% sodium hydroxide aqueous solution and 3% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to a solid-liquid ratio of 12.5 g / L to sodium hydroxide aqueous solution, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 70°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0070] S3: Weigh the cattail fiber and the ordinary qualitative filter paper according to the absolute dry weight ratio of 1:2, add them into 500 mL of deionized water, and use a high-speed mixer at 10,000 rpm for 30 minutes to obtain a composite suspension with a concentration of 2 g / L;

[0071] S4: The composite suspension is poured onto a 350-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 40° C. for 8 hours, and then vacuum dried at 80° C. for 12 hours to obtain a cattail fiber-based composite diaphragm.

[0072] Embodiment 4: This embodiment provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0073] S1: Scrape off the brown surface of the cattail, remove the root, scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root, and weigh the mass using a balance;

[0074] S2: Prepare equal volumes of 1% sodium hydroxide aqueous solution and 3% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to the solid-liquid ratio of cattail wool to sodium hydroxide aqueous solution of 1g / L, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 90°C in a water bath and keep it warm for 6 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 90°C in a water bath and keep it warm for 6 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 60°C for vacuum drying for 24 hours to obtain cattail wool fiber;

[0075] S3: Weigh the cattail fiber and the ordinary qualitative filter paper according to the absolute dry weight ratio of 1:9, add them into 500 mL of deionized water, and use a high-speed mixer at 12,000 rpm for 30 minutes to obtain a composite suspension with a concentration of 1.5 g / L;

[0076] S4: The composite suspension is poured onto a 200-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 25° C. for 12 hours, and then vacuum dried at 70° C. for 24 hours to obtain a cattail fiber-based composite diaphragm.

[0077] Example 5: This example provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0078] S1: Scrape off the brown surface of the cattail, remove the root, scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root, and weigh the mass using a balance;

[0079] S2: Prepare a sodium hydroxide aqueous solution with a mass concentration of 5% and a hydrogen peroxide aqueous solution with a volume ratio of 1:2 in a beaker respectively; weigh the cattail wool according to the solid-liquid ratio of cattail wool to sodium hydroxide aqueous solution of 25g / L, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 100°C in a water bath and keep it warm for 1h; pour the solution after the reaction into a sieve with an aperture of 400 mesh, and rinse it with deionized water 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 100°C in a water bath and keep it warm for 1h; pour the solution after the reaction into a sieve with an aperture of 400 mesh, and rinse it with deionized water 3 times; then place it in a vacuum drying oven at 80°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0080] S3: Weigh the cattail fiber and the ordinary qualitative filter paper according to the absolute dry weight ratio of 7:3, add them into 800 mL of deionized water, and use a high-speed mixer at 12000 rpm for 30 minutes to obtain a composite suspension with a concentration of 15 g / L;

[0081] S4: The composite suspension is poured onto a 400-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 50° C. for 6 hours, and then vacuum dried at 100° C. for 12 hours to obtain a cattail fiber-based composite diaphragm.

[0082] Example 6: This example provides a cattail fiber-based composite diaphragm, and the specific preparation method thereof comprises the following steps:

[0083] S1: Scrape off the brown surface of the cattail, remove the root, scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root, and weigh the mass using a balance;

[0084] S2: Prepare equal volumes of 3% sodium hydroxide aqueous solution and 4% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to the solid-liquid ratio of cattail wool to sodium hydroxide aqueous solution of 15 g / L, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 95°C in a water bath and keep it warm for 3 hours; pour the solution after the reaction into a sieve with an aperture of 300 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 95°C in a water bath and keep it warm for 6 hours; pour the solution after the reaction into a sieve with an aperture of 300 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 70°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0085] S3: Weigh the cattail fiber and the ordinary qualitative filter paper according to the absolute dry weight ratio of 4:6, add them into 1000mL deionized water, use a high-speed mixer at 11000 rpm, stir for 30 minutes to obtain a composite suspension with a concentration of 10g / L;

[0086] S4: The composite suspension is poured onto a 300-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 40° C. for 8 hours, and then vacuum dried at 85° C. for 12 hours to obtain a cattail fiber-based composite diaphragm.

[0087] Comparative Example 1: This comparative example provides a glass fiber diaphragm, which differs from Example 1 in that cattail fiber is replaced with commercial glass fiber, and its specific preparation method includes the following steps:

[0088] S1: Weigh the glass fiber and the ordinary qualitative filter paper in a ratio of 2:1, add them into 500 mL of deionized water, and stir them for 30 minutes using a high-speed stirrer at 10,000 rpm to obtain a composite suspension with a concentration of 2 g / L;

[0089] S2: The composite suspension is poured onto a 350-mesh polytetrafluoroethylene sieve and sieved. After sieving, the composite suspension is dried at 40° C. for 8 hours and then dried at 80° C. for 12 hours in a vacuum to obtain a glass fiber-based composite diaphragm.

[0090] Comparative Example 2: This comparative example provides a cattail fiber diaphragm, and its specific preparation method comprises the following steps:

[0091] S1: Scrape off the brown surface of the cattail, then remove the root, and scrape off the cattail fluff within the range of 1 / 4 to 3 / 4 of the length from the surface to the root (such as Figure 1 As shown), and use a balance to weigh the mass;

[0092] S2: Prepare equal volumes of 2.5% sodium hydroxide aqueous solution and 3% hydrogen peroxide aqueous solution in a beaker respectively; weigh cattail wool according to a solid-liquid ratio of 12.5 g / L to sodium hydroxide aqueous solution, add it to the sodium hydroxide aqueous solution, and after proper dispersion, heat the sodium hydroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; pour the rinsed sample directly into the hydrogen peroxide aqueous solution, and after proper dispersion, heat the hydrogen peroxide aqueous solution to 90°C in a water bath and keep it warm for 2 hours; pour the solution after the reaction into a sieve with an aperture of 200 mesh, and rinse it with deionized water for 3 times; then place it in a vacuum drying oven at 70°C for vacuum drying for 12 hours to obtain cattail wool fiber;

[0093] S3: adding the cattail fiber to 500 mL of deionized water, stirring for 30 minutes at 10,000 rpm using a high-speed stirrer to obtain a suspension with a concentration of 2 g / L;

[0094] S4: The suspension was filtered using a vacuum pump and funnel, and then dried at 40°C for 8 hours, and then vacuum dried at 80°C for 12 hours to obtain a cattail fiber separator.

[0095] Compared with Example 1, the cattail fiber membrane prepared in Comparative Example 2 has a relatively dense film, low porosity and poor electrochemical performance due to the filtration method adopted in the filtration method of suction filtration; while the filtration method adopted in the embodiment of the present invention is screening, which belongs to natural sedimentation, and the obtained composite membrane has better electrochemical performance.

[0096] Performance test: 1. The components of the ordinary qualitative filter paper, cattail wool (untreated), cattail wool fiber (treated) and the prepared composite membrane in Example 1 were determined by X-ray diffractometer (XRD). The instrument used was BRUKER AXS-D8 Discover. The test results are shown in the figure. Figure 2 As shown. Through analysis, the component of ordinary qualitative filter paper is cellulose, and the corresponding crystallinity is 80.1%. The crystallinity of cattail wool is low before treatment, and after impurity removal, it presents a cellulose structure with a crystallinity of 75.0%. Example 1, which is a composite of two fibers, still maintains a cellulose component with high crystallinity. The high crystallinity of cellulose makes the tensile strength (3.2-40.6Mpa) of the composite diaphragm prepared in this embodiment of the present invention better than that of the commercially available glass fiber diaphragm (<1Mpa).

[0097] 2. The morphology of the composite membranes prepared in Examples 1-3 and Comparative Example 1 was observed using a scanning electron microscope (SEM). The instrument used was HITACHI-SU8020. The observation results are as follows: Figure 3-Figure 7 As shown. Figure 3It can be found that the cattail fibers after impurities removal present a flat structure, and the raised edges in the middle and the two sides of the edges form relatively symmetrical grooves. The nanofibers with a diameter of about 50nm are obtained by strong dispersion of ordinary qualitative filter paper. With the help of physical crosslinking and hydrogen bonding, the cattail fibers can be well combined with the filter paper nanofibers, which ensures that the composite diaphragm has a certain mechanical strength and flexibility. The cross section of the composite diaphragm obtained in Example 1-3 (such as Figure 4-Figure 6 As shown in Figure 1, both of them present a multi-layer porous structure. By comparison, it can be seen that the thickness of the composite membrane can be adjusted by changing the composite ratio of cattail fiber and qualitative filter paper. Figure 3 As shown) and Comparative Example 1 (as Figure 7 As shown in the figure, the filter paper fibers partially cover the grooves of the cattail fibers and form a network structure with different pore sizes above the grooves. The pores of the filter paper fibers after being composited with the smooth glass fibers are smaller, indicating that the comparative example 1 of the embodiment 1 has better liquid absorption and retention capabilities. Through testing, it is found that the electrolyte loading rate of the embodiment 1 is 596.3%, while the electrolyte loading rate of the comparative example 1 is 430.7%.

[0098] 3. The electrolyte wettability of the composite membranes prepared in Examples 1-3 was analyzed using a contact angle meter. The instrument used was Shanghai Zhongchen-JC2000D1. The results are as follows: Figure 8 The composite diaphragms prepared in the embodiments of the present invention have good wettability to the electrolyte and can completely absorb the electrolyte within 4 seconds.

[0099] 4. Commercial sodium vanadium phosphate was used as the positive electrode and sodium sheet as the negative electrode, and the composite diaphragm prepared in Examples 1-3 and the existing commercially available glass fiber diaphragm (Whatman GF / D) were respectively assembled into 2032 button cells in a Braun glove box filled with argon. Then, the charge and discharge tests were carried out in the voltage range of 2.2-3.8V (1C=117mA / g). The results are as follows: Fig. 9 , Fig.10 As shown. Fig. 9 It can be seen that the composite membranes prepared in the embodiments of the present invention have better cycle stability than the glass fiber membranes. The capacity retention rate after 500 cycles at 1C is above 95%, while that of the glass fiber membrane is only 91.6%. Fig.10 In the rate performance shown, some of the composite membranes prepared in the embodiments of the present invention are similar to glass fiber membranes.

[0100] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a cattail fiber-based composite diaphragm, characterized in that: The following steps are involved: Dispersing cattail wool in a sodium hydroxide solution and soaking it at high temperature to obtain a first dispersion; After filtering the first dispersion, the dispersion is dispersed in a hydrogen peroxide solution and immersed at high temperature to obtain a second dispersion; The second dispersion is filtered and dried to obtain cattail fibers; The cattail fibers and the qualitative filter paper are dispersed in a solvent to obtain a composite suspension; The composite suspension is sieved and dried to obtain a cattail fiber-based composite diaphragm.

2. The method for preparing a cattail fiber-based composite diaphragm according to claim 1, characterized in that: The method for obtaining cattail wool comprises the following steps: Scrape off the surface layer of the cattail sticks and remove the roots to get the cattail fluff.

3. The method for preparing a cattail fiber-based composite diaphragm according to claim 1, characterized in that: The cattail fluff is dispersed in a sodium hydroxide solution and then soaked at high temperature. The temperature of the high temperature soaking is 90-100°C.

4. The method for preparing a cattail fiber-based composite diaphragm according to claim 1 or 3, characterized in that: The sodium hydroxide solution is an aqueous solution of sodium hydroxide, and its mass concentration is 1%-5%; the material-liquid ratio of cattail wool to the sodium hydroxide solution is 1-25g / L.

5. The method for preparing a cattail fiber-based composite diaphragm according to claim 1, characterized in that: After filtering the first dispersion, it is dispersed in a hydrogen peroxide solution and then soaked at high temperature: the filtering method is to place the first dispersion in a sieve with a pore size of 200-400 mesh and rinse it with deionized water; the high temperature soaking temperature is 90-100°C.

6. The method for preparing a cattail fiber-based composite diaphragm according to claim 1 or 5, characterized in that: The hydrogen peroxide solution is a water solution of hydrogen peroxide, and its mass concentration is 3%-5%; the material-liquid ratio of cattail wool to hydrogen peroxide solution is 1-50g / L.

7. The method for preparing a cattail fiber-based composite diaphragm according to claim 1, characterized in that: The solvent is deionized water; the total concentration of cattail fiber and qualitative filter paper in the composite suspension is 1.5-15 g / L; the absolute dry weight ratio of cattail fiber and qualitative filter paper in the suspension is 1:9-7:

3.

8. The method for preparing a cattail fiber-based composite diaphragm according to claim 1, characterized in that: In the steps of sieving and drying the composite suspension, the aperture of the sieve used for sieving is 200-400 meshes; the drying method is to dry at 25-50°C and then to vacuum dry at 70-100°C.

9. A cattail fiber-based composite diaphragm prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the cattail fiber-based composite diaphragm as claimed in claim 9 in a sodium ion battery.